BENTUK DAN PROPORSI PADA PERWUJUDAN ARSITEKTUR VERNAKULAR BUGIS - Sani, Andi Asrul; Supriyadi, Bambang; Rukayah, R.Siti (Jurnal Teknik Sipil dan Perencanaan, 2015)
This research lifting Vernacular Architectural Bugis with case studies Bola Soba State Watampone as part of the work of Duke ( King ). The issue building design process Bola Soba into focus through all proportions study's components constituent. Base his study , in addition to an understanding of the essence vernacular, the need of understanding also his tectonics, tradition ( build ) Architecture Bugis and rules proportion.the feel aesthetics in architecture is based on the elements and principles of design that can be explained rationally one of which is the principle of proportion. Leaning on his study approach: all characteristics of vernacular ( Bugis ) , visual and numerical portrait (measurement dimension ) objects. Images are visual and numerical reference database for reconstruction  groups object to the graphic data and figures. Analysis of calculation of the ratio  proportion to his assisted Software Microsoft Excel and SPSS ( Statistical Product and Service Solution). The findings of this research form the basic of the ratio of the amount used as a reference for comparison of the parts of the building detail in the building in the city of Bola Soba in Watampone. Proportion 1 : 1.23 with Sulapa Appa element and is believed to be the final findings as the basic for the size calculation of the proportion of the building Bola Soba. Implications of the findings could be early reference ( hypothesis ) , that the work of vernacular architecture Bugis embodiment has a basic size its design. Reference process is certainly still need to be explored with further research, including the work of other vernacular which created by the Duke / King Bugis. In historically, kingdom Bugis had been a formidable kingdom in his day which civilization has its own form of architecture heritage building. There are four great kingdoms that became the Bugis area is the kingdom of Luwu, kingdom of Bone, the kingdom of Soppeng and Wajo.Penelitian ini mengangkat Arsitektur Vernakular Bugis dengan studi kasus Bola Soba Kota Watampone sebagai wujud karya kalangan Bangsawan (Raja).Persoalan proses perancangan bangunan Bola Soba menjadi fokus telaah melalui ke-proporsi-an komponen-komponen pembentuknya.Dasar telaahnya, selain pemahaman tentang esensi ke-vernakular-an, perlu pemahaman pula sisi ke-tektonika-annya, tradisi (membangun) Arsitektur Bugis dan kaidah proporsi.Rasa estetika dalam arsitektur didasarkan pada elemen –elemen dan prinsip-prinsip perancangan yang bisa dijelaskan secara rasional salah satunya adalah prinsip proporsi. Pendekatan studinya bersandar pada : ke-ciri-an vernakular (Bugis), potret visual dan numerik (pengukuran dimensi) obyek. Potret visual dan numerik merupakan database rujukan untuk me-rekonstruksi-kan gugus obyek ke data grafis dan angka. Analisis perhitungan rasio ke-proporsi-annya dibantu perangkat lunak Microsoft Excel dan SPSS (Statistical Product and Service Solution). Temuan penelitian ini berupa besaran rasio dasar yang digunakan sebagai acuan perbandingan bagian-bagian detail bangunan dalam bangunan Bola Soba di Kota Watampone.Proporsi 1:1,23 dengan elemen Sulapa Appa menjadi temuan akhir dan diyakini sebagai dasar ukuran perhitungan proporsi dalam bangunan Bola Soba.Implikasi temuannya bisa menjadi referensi awal (hipotesis), bahwa perwujudan karya arsitektur vernakular Bugis memiliki dasar ukuran dalam proses perancangannya.Referensi ini tentunya masih perlu didalami dengan penelitian lanjutan, termasuk karya vernakular lain yang dikreasi oleh kalangan Bangsawan/Raja Bugis.Secara historis,kerajaan Bugis pernah menjadi kerajaan yang tangguh di zamannya memiliki peradaban tersendiri berupa peninggalan Arsitektur Bangunan.Ada empat kerajaan besar yang menjadi wilayah Bugis yaitu Kerajaan Luwu,Kerajaan Bone,Kerajaan Soppeng dan Wajo. This research lifting Vernacular Architectural Bugis with case studies Bola Soba State Watampone as part of the work of Duke ( King ). The issue building design process Bola Soba into focus through all proportions study's components constituent. Base his study , in addition to an understanding of the essence vernacular, the need of understanding also his tectonics, tradition ( build ) Architecture Bugis and rules proportion.the feel aesthetics in architecture is based on the elements and principles of design that can be explained rationally one of which is the principle of proportion. Leaning on his study approach: all characteristics of vernacular ( Bugis ) , visual and numerical portrait (measurement dimension ) objects. Images are visual and numerical reference database for reconstruction  groups object to the graphic data and figures. Analysis of calculation of the ratio  proportion to his assisted Software Microsoft Excel and SPSS ( Statistical Product and Service Solution). The findings of this research form the basic of the ratio of the amount used as a reference for comparison of the parts of the building detail in the building in the city of Bola Soba in Watampone. Proportion 1 : 1.23 with Sulapa Appa element and is believed to be the final findings as the basic for the size calculation of the proportion of the building Bola Soba. Implications of the findings could be early reference ( hypothesis ) , that the work of vernacular architecture Bugis embodiment has a basic size its design. Reference process is certainly still need to be explored with further research, including the work of other vernacular which created by the Duke / King Bugis. In historically, kingdom Bugis had been a formidable kingdom in his day which civilization has its own form of architecture heritage building. There are four great kingdoms that became the Bugis area is the kingdom of Luwu, kingdom of Bone, the kingdom of Soppeng and Wajo.